Autofiction and the Law: Legal Scandals in Contemporary French Literature. Issue 1 (1st January 2018) - Edwards, Natalie
ABSTRACT: This article compares two legal cases in France that involved works of autofiction. Camille Laurens and Christine Angot were both accused of atteinte à la vie privée on the basis of their representation of others in literary works. Laurens was found innocent and Angot guilty. This article compares the texts, the ways in which their authors articulate their identities as contemporary writers, and arguments advanced in their trials. At a time at which the truth is hotly contested, it examines what is at stake in the current spate of legal cases involving literature and reflects upon the current relationship between law and life writing.